Quantifying Question Asking in Young Autistic Children: Exploring the Role of Context. - Armstrong, Brianna; Arunachalam, Sudha; Nehilla, Lauren; Luyster, Rhiannon (Seminars in Speech & Language, 2026)
Questions are an important component of social communication. Autistic children experience difficulties in social communication, and question asking is a common target of services. We know little about how context shapes question asking in autistic children. The current study quantifies the frequency (rate per minute), form (wh-, yes/no, intonation), and function (information-seeking, directive, initiation/maintenance) of questions produced by autistic children (n = 15; mean age = 5.6 years) in two social contexts: a semi-structured activity (the "tablet task") and unstructured play (a naturalistic play session). Autistic children asked slightly more questions in the play session (M =1.35 questions/minute) than in the tablet task (M = 0.81 questions/minute), but there was no significant difference between conditions (effect size = 0.36). For question form, children asked wh-questions at similar rates across contexts, but they asked significantly more yes/no and intonation questions in the play session (effect sizes = 0.01, 0.62, 0.85, respectively). Finally, in function, children's use of information-seeking questions was similar across contexts, but they used significantly more directive and initiation/maintenance questions in the play session (effect sizes = 0.008, 0.82, 0.80, respectively). These findings offer important considerations for the assessment of question asking in autistic children.